Model Pembelajaran Rollenspiel untuk Meningkatkan Keterampilan Berbicara Bahasa Jerman Siswa - Irmawati Irmawati; Misnah Mannahali (Makassar State University, 2019)
The purpose of this study was to know the effectiveness of the Rollenspiel model in increasing student’s speaking German skill. This study used quasy-experiment approach. Data was collected using speaking skill test. The sample in this study was random sampling, namely students of class XI IPA 1 which amounted to 20 students as an experimental class and students of class XI IPA 2 totaling 21 students as a control class. Data were analyzed by using t-Test analysis. The result of data analysis shows that th 4,28> tt 2,023 at significant level of 0.05. The results showed that Rollenspiel learning model is effectively used in the skill of speaking of German.